Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1007/bf00636619
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of static and dynamic exercise

Abstract: The cardiovascular response to static exercise has often been quantified on the basis of a comparison between static handgrip and dynamic cycling exercise. It is then difficult to make precise comparisons because the physical units of work are not compatible. If the data from dynamic exercise can be used to predict the cardiovascular response to zero movement (static exercise) this would suggest that static exercise is not fundamentally different from dynamic exercise. Using leg extension exercise which lasted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 11 publications
0
18
1
2
Order By: Relevance
“…The increase in cardiac output results primarily from an accelerated heart rate. Stroke volume during static hand grips at loads greater than 20% of the maximal voluntary contraction (MVC) can be significantly reduced due to the increased left ventricular afterload (Bezucha et al, 1982; Chapman and Elliot, 1988). …”
Section: Introductionmentioning
confidence: 99%
“…The increase in cardiac output results primarily from an accelerated heart rate. Stroke volume during static hand grips at loads greater than 20% of the maximal voluntary contraction (MVC) can be significantly reduced due to the increased left ventricular afterload (Bezucha et al, 1982; Chapman and Elliot, 1988). …”
Section: Introductionmentioning
confidence: 99%
“…The influence of each mechanism on the heart rate and blood pressure response to exercise depends on factors like recruited muscle mass, muscle fiber type, exercise intensity and the exercise mode [10-12]. Early literature that compared the cardiovascular response to static and dynamic muscular actions indicated a strong increase in heart rate (HR) and systolic arterial pressure (SBP), and minor changes in diastolic arterial pressure (DBP) during dynamic work, while isometric work is thought to induce only modest increases of HR but marked increases in SBP and in particular DBP [13-18]. However, the generality of these observations is limited, because a) mostly cardiovascular effects of static (SE) and dynamic exercise (DE) had been studied separately; b) the quantification and thus the equating of workload during different exercise modes is difficult [18]; and c) often the compared muscles were of different size and location.…”
Section: Introductionmentioning
confidence: 99%
“…Early literature that compared the cardiovascular response to static and dynamic muscular actions indicated a strong increase in heart rate (HR) and systolic arterial pressure (SBP), and minor changes in diastolic arterial pressure (DBP) during dynamic work, while isometric work is thought to induce only modest increases of HR but marked increases in SBP and in particular DBP [13-18]. However, the generality of these observations is limited, because a) mostly cardiovascular effects of static (SE) and dynamic exercise (DE) had been studied separately; b) the quantification and thus the equating of workload during different exercise modes is difficult [18]; and c) often the compared muscles were of different size and location. Static vs. dynamic contractions of identical small muscles, e. g. during submaximal handgrip exercise, elicited similar HR and BP response [19], while it was shown that submaximal isometric contractions of larger muscles (e. g. knee extensors/flexors) at 40 % of maximum effort can induce lower HR and BP responses than isokinetic or isotonic contractions [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além do estímulo químico liberado pela a realização dos exercícios, acredita-se que a oclusão promove uma dor local, o que pode contribuir para ANSP se manter elevada neste período, uma vez que em outro estudo, houve aumento da ANSP na oclusão, mesmo após intensidades baixas de exercício dinâmico em que a ANSP não se alterou 109. Estudos que compararam as respostas ao exercício estático e dinâmico em indivíduos saudáveis verificou-se um maior aumento de pressão arterial durante o exercício estático e um maior aumento de FC durante o exercício dinâmico 112,113 . Isso ocorre uma vez que a estimulação química a partir dos metabólitos liberados no exercício estático promove uma resposta excitatória maior do que a estimulação mecânica gerada pelos exercícios dinâmicos 114 . No presente estudo, quando comparamos os valores das variáveis obtidas nos exercícios estático e dinâmico, observamos que os dois tipos de exercícios promovem resposta semelhante Um fato que deve ser levado em conta é que no presente estudo a medida da ANSP foi realizada no nervo fibular da perna cuja musculatura não foi exercitada durante a realização das manobras excitatórias.…”
Section: Exercícios Estático E Dinâmico Com "Handgrip"unclassified